2008
DOI: 10.1186/1546-0096-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating score distributions in the revised Dutch version of the Childhood Health Assessment Questionnaire

Abstract: Objectives: Evaluating the original, and the revised version of the Dutch Childhood Health Assessment Questionnaire (CHAQ). To explore the effect of different score calculation methods and eight more challenging items as proposed by Lam et al. (2004) on the score distribution in a population of patients with Juvenile Idiopathic Arthritis (JIA). Methods:Two convenience samples of 59 and 31 children with JIA were studied. Box-andwhisker plots and the Kolmogorov-Smirnov (K-S) one-sample test of normality were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
2
11
1
Order By: Relevance
“…This finding is in accordance with the study of Ouwerkerk et al [10], Lam et al [7] and Van Dijk et al [11] that both show a reduced number of patients at the ceiling.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the study of Ouwerkerk et al [10], Lam et al [7] and Van Dijk et al [11] that both show a reduced number of patients at the ceiling.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, values of the CHAQ38 were most improved with the CAT1 in patients and with the CAT2 in controls, even though slightly fewer controls completed this response model. However, unlike the findings of others (11,(15)(16)(17), showing a reduction in the ceiling effect of no less than 15% when using CHAQ38 instead of CHAQ30, we found that the ceiling effect was still present in both CHAQ versions. However, the ceiling effect was most reduced, but not avoided, when using the CAT2 response model in both study groups.…”
Section: Discussioncontrasting
confidence: 86%
“…Others have examined the revised CHAQ versions in children with JIA and shown a significantly improved sensitivity and a diminished ceiling effect using the CHAQ38 (15)(16)(17), but with less convincing results with the CAT2, compared to the CAT1 with a simplified scoring model (15)(16)(17) (Figure 1). …”
mentioning
confidence: 97%
“…Disability was measured using the Dutch version of the Childhood Health Assessment Questionnaire (C-HAQ38) [28], which measured functional impairment in 9 domains. Scores ranged from 0 to 3, where 0 stands for no impairment and 3 for maximum impairment.…”
Section: Methodsmentioning
confidence: 99%